The Influence of Motivating Teachers and Organizational Culture on Students' Social Sciences Learning Outcomes at UPT SPF SD Inpres Baraya 1 Makassar - Ernawati, Ernawati; Yahya, Muh; Devilla, Rego (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The aims of this research are: (1) To determine the influence of driving teachers on students' social studies learning outcomes at UPT SPF SD Inpres Baraya I. (2) To determine the influence of organizational culture on students' social studies learning outcomes at UPT SPF SD Inpres Baraya I. (3) ) To determine the influence of driving teachers and organizational culture together on students' social studies learning outcomes at UPT SPF SD Inpres Baraya I. This research is a quantitative research with a verification research design using a correlational descriptive approach with data collection techniques through questionnaires. The number of respondents was 90 people. The results of this research show that (1) There is a positive and significant influence between driving teachers and the social studies learning outcomes of UPT SPF SD Inpres Baraya I students. The contribution of driving teachers to the social studies learning outcomes of UPT SPF SD Inpres Baraya I students is in the medium category. (2) There is a positive and significant influence between organizational culture and the social studies learning outcomes of UPT SPF SD Inpres Baraya I students. The contribution of organizational culture to the social studies learning outcomes of UPT SPF SD Inpres Baraya I students is in the medium category. (3) There is a positive and significant influence between the driving teacher variable and the organizational culture variable on the social studies learning outcomes of UPT SPF SD Inpres Baraya I students. The contribution of driving teachers and organizational culture together to the social studies learning outcomes of UPT SPF SD Inpres Baraya I students is significant. is in the medium category.